2017
DOI: 10.3329/akmmcj.v7i2.31639
|View full text |Cite
|
Sign up to set email alerts
|

Post-Surgical Outcomes of Dorsolateral Onlay Urethroplasty

Abstract: Background: The standard management of urethral strictures involving the anterior urethra is dorsal onlay buccal mucosa augmentation urethroplasty. This requires circumferential mobilisation of the urethra, which might cause ischemia of the urethra in addition to chordee. In this research, we managed the anterior urethral stricture, applying a dorsolateral onlay urethroplasty.Methodology: This prospective study was conducted in the Department of Urology, BIRDEM General Hospital& some private hospitals from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(9 reference statements)
0
1
1
Order By: Relevance
“…Kulkarni et al shows in the study of 24 patients with mean follow up of 22 months, 92% successful outcome where 02 (8%) were failed 13 . In our study, mean pre and postoperative Qmax were 6.75 ml/s and 23.47 ml/s whereas Prabha et al and Mowladad et al showed 6.5 ml/s and 24 ml/s, 6.08 ml/s and 29.04 ml/s respectively in their studys 12,14 . Prabha et al, Tapas Majhi, Prakasa et al, reported that most common complication was wound infection (10%, 10%, 11.4%) which is also similar to us (9.4%) 4,12,15 .…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Kulkarni et al shows in the study of 24 patients with mean follow up of 22 months, 92% successful outcome where 02 (8%) were failed 13 . In our study, mean pre and postoperative Qmax were 6.75 ml/s and 23.47 ml/s whereas Prabha et al and Mowladad et al showed 6.5 ml/s and 24 ml/s, 6.08 ml/s and 29.04 ml/s respectively in their studys 12,14 . Prabha et al, Tapas Majhi, Prakasa et al, reported that most common complication was wound infection (10%, 10%, 11.4%) which is also similar to us (9.4%) 4,12,15 .…”
Section: Discussioncontrasting
confidence: 62%
“…Regarding postoperative patients compliance, 28 patients (87.5%) were satisfied with surgery upto 22.4 months mean follow up. In their study, they were reported 94%, 85%, 96%, 76% and 94.2% success rate respectively through this approach with a mean follow up of 19, 22.7, 18, 18 and 12 months 11,12,14,15 . Kulkarni et al shows in the study of 24 patients with mean follow up of 22 months, 92% successful outcome where 02 (8%) were failed 13 .…”
Section: Discussionmentioning
confidence: 93%